Interdisciplinarity, Collective Intelligence, and the Role of the Humanities and Social Sciences in Greece’s Socioeconomic Development - Gavroglou, Stavros (HAPSc Policy Briefs Series, 2025)
This article explores the complex and underexamined relationship between the Humanities and Social Sciences (HSS) and Greece’s economic and social development. Against a policy landscape dominated by a preference for Science, Technology, Engineering, and Mathematics (STEM), this article contends that the declining status of HSS in Greece is not an inevitable consequence of labour market trends, but rather a manifestation of a narrow policy focus. Using evidence from Greek and EU labour market data, this study highlights how the underutilization of high-skill labour, including but not limited to HSS graduates, reflects broader structural challenges within Greece’s productive model. The article argues that interdisciplinarity and collective intelligence (two concepts where HSS have a comparative advantage) are indispensable to the transformation of the Greek economy. Through empirical evidence, comparative statistics, theoretical analysis, historical context, and cultural commentary, this contribution calls for a reinvigoration of HSS as a central pillar of sustainable and inclusive development in the era of technological complexity and artificial intelligence.